Mechanism and effect of microplastics toxicity in aquatic system - Wu, Shiqi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In recent years, the increasingly serious plastic waste pollution has gradually become a global problem. Microplastics (MPs) as an emerging pollutant has received attention. MPs are toxic to humans and many other organisms, and they can accumulate in organisms and amplify their toxic effects through the food chain, thus causing damage to marine biodiversity. Moreover, the seafood provided by the ocean is an important source of food for human beings, and MPs accumulated in fish and crustaceans may be ingested by human beings and cause damage to the digestive system, immune system, respiratory system, nervous system and reproductive system. With the increasing severity of marine plastic pollution, the effect of MPs on aquatic organisms should be of greater concern. By analyzing in vitro or in vivo experimental studies on microalgae, corals, and fish, the effects of MPs on microalgae photosynthesis, coral growth, and fish growth and reproduction were investigated, as well as the oxidative stress induced by MPs in these organisms. It is hoped that it will help people to understand the harmful effects of MPs on aquatic organisms from these three organisms, so that the toxic effects of MPs can be taken seriously.